Trends in oral small-molecule drug discovery and product development based on product launches before and after the Rule of Five. Issue 2 (February 2023) - Stegemann, Sven; Moreton, Chris; Svanbäck, Sami; Box, Karl; Motte, Geneviève; Paudel, Amrit
Graphical abstract: Highlights: Orally delivered drug products gradually continue to exceed the Rule-of-five on Molecular Weight and clogP. New predictive descriptors and tools, advanced chemistry and lead optimization are being applied. Formulation and drug delivery technology play an important role in oral drug product development. An integrated approach is required for candidate selection and drug product development of beyond the Rule-of-five compounds. Abstract : In 1997, the 'Rule of Five' (Ro5) suggested physicochemical limitations for orally administered drugs, based on the analysis of chemical libraries from the early 1990s. In this review, we report on the trends in oral drug product development by analyzing products launched between 1994 and 1997 and between 2013 and 2019. Our analysis confirmed that most new oral drugs are within the Ro5 descriptors; however, the number of new drug products of drugs with molecular weight (MW) and calculated partition coefficient (clogP) beyond the Ro5 has slightly increased. Analysis revealed that there is no single scientific or technological reason for this trend, but that it likely results from incremental advances are being made in molecular biology, target diversity, drug design, medicinal chemistry, predictive modeling, drug metabolism and pharmacokinetics, and drug delivery.